Legal protection of online loan recipients based on financial services authority - Myranika, Annie (Linguistics and Culture Review, 2021)
This study aims to determine the form of legal protection, dispute resolution, and provide legal understanding. The normative research method using a qualitative approach describes legislation and a case approach, and Law Number 21 of 2011 concerning the Financial Services Authority, Law Number 19 of 2016 ITE, and OJK Number 77/POJK.01/2016 concerning Borrowing Services. . Data collection techniques through (1). Interview, (2). Surveys (3). Documentation study. Conclusion (1). Many customers are victims as users of unlicensed services. (2). Efforts to protect customers against the implementation of OJK services (3). Cooperating with the Indonesian Joint Funding Fintech Association (4). Determination of the upper limit on loan interest and code of conduct for the loan collection process, (5). OJK cooperates with the Ministry of Communication and Information.